2006
DOI: 10.1101/gad.382306
|View full text |Cite
|
Sign up to set email alerts
|

Rep and PriA helicase activities prevent RecA from provoking unnecessary recombination during replication fork repair

Abstract: The rescue of replication forks stalled on the template DNA was investigated using an assay for synthetic lethality that provides a visual readout of cell viability and permits investigation of why certain mutations are lethal when combined. The results presented show that RecA and other recombination proteins are often engaged during replication because RecA is present and provokes recombination rather than because recombination is necessary. This occurs particularly frequently in cells lacking the helicase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 54 publications
4
86
0
Order By: Relevance
“…2). However, RecA is proposed to both promote fork regression and to process regressed forks (8). Consistent with this model, we found that MDS42 lexA3 is hypersensitive to BCM (MIC <25 μg/mL BCM) ( Fig.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…2). However, RecA is proposed to both promote fork regression and to process regressed forks (8). Consistent with this model, we found that MDS42 lexA3 is hypersensitive to BCM (MIC <25 μg/mL BCM) ( Fig.…”
Section: Resultssupporting
confidence: 76%
“…However, they can only rarely result in fork collapses, which are highly damaging to cells (3,(7)(8)(9)11). Our data suggest that Rho removes TEC ahead of replisomes, preventing collision, fork collapse, and DSB formation.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations